Stabilisation of extracellular matrix is crucial to rapamycin-mediated life span increase in Marfan mgR/mgR mice - Zaradzki, Marcin; Rehberg, Franziska; Zwaans, Vanessa; Hecker, Markus; Karck, Matthias; Arif, Rawa; Soethoff, Jasmin; Wagner, Andreas H. (Biochemical pharmacology, 2025)
Marfan syndrome is a hereditary connective tissue disorder caused by heterozygous mutations in the fibrillin-1 gene (FBN1) and altered TGF-β signalling. Life-threatening complications involve thoracic aortic aneurysms (TAA) and dissections due to the disruption of microfibrillar assembly in the aortic wall. We previously demonstrated that Rapamycin, a typical mTOR pathway inhibitor, limits the ascending aorta elastolysis and expansion, significantly increasing lifespan in an established murine model of Marfan syndrome (Zaradzki et al., Biochem Pharmacol 2022). This study aimed to investigate how mTOR inhibition stabilises the aorta in fibrillin-1 hypomorphic mgR/mgR mice and previously observed increased life expectancy. We used antibody microarrays to detect protein expression in the proximal thoracic aorta of sham or rapamycin-treated male and female mgR/mgR mice immediately after the two-week treatment. Immunofluorescence staining was performed to visualize and quantify protein expression in the ascending thoracic aorta and arch four weeks after the short-term rapamycin treatment was completed. We showed that rapamycin significantly increased the abundance of extracellular matrix (ECM) proteins like cytokeratin-18 and betaglycan, also known as the TGF-β type 3 receptor (TGFBR3). In addition, it raises the abundance of aggrecanase-2 (ADAMTS5) and xylosyltransferase-1 proteins, enzymes involved in ECM remodelling and homeostasis. In conclusion, rapamycin affects the composition and organization of key ECM components, which determine the structure-function relationships in the aorta, thereby maintaining the balance critical for the increase in life expectancy. Using mTOR modulators for targeted therapy may help to prevent aortic complications of MFS and improve clinical outcomes.
Online verfügbar: 27. Februar 2025, Artikelversion: 01. März 2025
Gesehen am 12.08.2025